Peningkatan Literasi Pengelolaan Sampah berbasis Zero Waste Management pada Rumah Tangga Keluarga di Desa Duren - Muzayanah, Fety Nurlia; Miharja, Rediawan; Muhammad, Rabhi Fathan; Wiliyanti, Rizke; Almanfarisi, Muhammad Gibran; Burhanudin, Mochamad Faishal; Anggraeni, Anggraeni; Shofwaana, Reyza Ardelia (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
Duren Village is one of the villages in Klari Sub-district with the highest population density per km2 in Klari Sub-district, the population density is is positively correlated with the rate of household waste production. With this influence, good waste management is needed, but Duren Village must face a problem in this regard in the form of Duren Village must face problems in this regard the form of the lack of knowledge and skills of partners in processing household waste and high population density and limited open land. The implementation of this activity was carried out to help Duren Village face these problems with the method of socialization and training related to household waste management based on zero waste management. With the implementation of this activity, the results were obtained increased literacy about household waste management of the participants with sustainability.